2003
DOI: 10.1111/j.1524-6175.2003.02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Surveillance of Hypertension in Firefighters

Abstract: The authors evaluated blood pressure and antihypertensive medication use in 334 firefighters in an occupational medical surveillance program. Firefighters received written summaries of their examination results, including blood pressures, and were encouraged to see their personal physicians for any abnormal results. The mean age of the participants was 39 years, and the vast majority were men (n=330). The prevalence of hypertension was 20% at baseline (1996), 23% in 1998, and 23% in 2000. Among firefighters wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 32 publications
6
22
3
Order By: Relevance
“…In a population of volunteer firefighters, we confirmed what other studies have reported; firefighters may have increased cardiovascular risk [4,5,7]. The volunteer firefighters in our study were inactive, had low fitness levels, were overweight or obese, and had prehypertension.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In a population of volunteer firefighters, we confirmed what other studies have reported; firefighters may have increased cardiovascular risk [4,5,7]. The volunteer firefighters in our study were inactive, had low fitness levels, were overweight or obese, and had prehypertension.…”
Section: Discussionsupporting
confidence: 94%
“…The average weight of the firefighting PPE was 54.2 3.5 lbs. The volunteer firefighters had several cardiovascular risk factors, confirming what other studies have found [7,21]. The average BMI of the firefighters was 30.8 6.3 kg/m 2 , with most participants being overweight (23%) or obese (44%), similar to other studies [21] The average resting BP of the firefighters was 129.4/75.1 mmHg, which is classified as prehypertension.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…We have previously shown that hypertension and dyslipidemia are often inadequately treated among professionally active Massachusetts firefighters and that uncontrolled hypertension is associated with a higher risk of adverse changes in employment status. [15][16][17] Therefore, we believe that risk factor screening alone is insufficient, and fire department medical programs should include incentives to promote more aggressive risk factor reduction. These should include measures for progressively controlling hypertension, 17,26 which is a treatable illness yet one whose failure to control accounted for almost 10% of heart retirements and most likely contributed to others.…”
Section: Discussionmentioning
confidence: 98%